Coastal aeolian sediment transport in an active bed surface layer: Tracer study and conceptual model. Issue 13 (18th August 2022) - Uphues, Charlotte F. K.; van IJzendoorn, Christa O.; Hallin, Caroline; Pearson, Stuart G.; van Prooijen, Bram C.; Miot da Silva, Graziela; de Vries, Sierd
Abstract: Coastal aeolian sediment transport is influenced by supply‐limiting factors caused by sediment sorting by grain size. Sorting processes can lead to coarsening of the bed surface and influence the formation of aeolian ripples. However, the influence sorting processes and bedforms might have on the magnitude of the transport is not fully understood. This study explores sorting processes and their influence on the magnitude and mode of aeolian transport by using sediment tracers. Sand was painted in different colors according to particle size and placed on a supratidal beach in Noordwijk, the Netherlands. Several experiments were conducted with varying wind speeds. Surface sampling and cameras tracked the sand color movement on the bed surface, and wind velocity was measured. The tracer experiments showed that ripples developed in moderate wind conditions. Once the ripples had formed, the supply of finer tracer grains in the downwind direction decreased over time, while the supply of coarser grains remained constant. A linear relationship between ripple migration speed and wind speed was found. For higher wind speeds, no ripples or differences in transport of grain size fractions were observed. Instead, alternating phases of erosion and deposition of the bed surface were observed, which could not be related to local variations in wind velocity. Based on these results and literature, a conceptual model was developed for an active bed surface layer with two transport regimes corresponding to moderate (I) and high (II) wind speeds. The conceptual model is intended to guide the selection of aeolian sediment transport models as a function of wind speed, bed characteristics, and upwind sediment supply. For Regime I, transport could be modeled using a linear relationship between sediment transport and wind speed and for Regime II using a third power relationship in combination with a process‐based model accounting for supply limitations. Abstract : Tracer experiments showed significant differences in the behavior of the bed surface between moderate and high wind speeds. Moderate wind speeds caused aeolian ripple development and grain size sorting, whereas higher wind speeds caused temporary phases of erosion and deposition, which could not be related to local gradients in wind speed. These insights on the interplay between sediment sorting, bedform development, and aeolian transport were integrated into a conceptual model to improve aeolian transport predictions.